In vivo model of Hirschsprung-associated enterocolitis using benzalkonium chloride (Faculty of Medicine Universitas Indonesia, 2021)
BACKGROUND Hirschsprung-associated enterocolitis (HAEC) is a life-threatening complication of Hirschsprung’s disease. Studies using animal models on the pathogenesis of HAEC are limited. Thus, this study aimed to establish a rat model of HAEC using topical application of 0.1% benzalkonium chloride (BAC) in the sigmoid colon. METHODS 55 male Sprague Dawley rats aged 10−12 weeks old were separated into 11 groups. The control group (n = 5) was euthanized on day-7, and the other 10 groups (n = 5 in each group) treated with 0.1% BAC in the sigmoid colon for 15 min to induce Hirschsprung’s disease were euthanized on day-7, -10, -12, -14, -17, -19, -21, -23, -25, and -28. The sigmoid colon was excised, fixed in formalin, and sectioned for histological examinations with hematoxylin and eosin staining. The degree of HAEC was compared within all groups. RESULTS Rats that were sacrificed on day-7 to -12 showed the 1st degree or early HAEC, which was most likely caused by BAC application. The 2nd degree of HAEC occurred in rats that were sacrificed on day-14 that showed a macrophage infiltration in the sigmoid colon, thus fulfilled the initial criteria for HAEC (p = 0.0025 versus control). The degree of enterocolitis increased with time, and the highest degree was found in rats that were sacrificed on day-28 (p<0.001 versus control). CONCLUSIONS Topical application of 0.1% BAC for 15 min was successfully produced HAEC model in rats, which was occurred on day-14 after the application. This model provides a useful resource for further research on the pathogenesis of HAEC.